Targeting SUMOylation in Plasmodium as a Potential Target for Malaria Therapy - Sumam de Oliveira, Daffiny; Kronenberger, Thales; Palmisano, Giuseppe; Wrenger, Carsten; de Souza, Edmarcia Elisa (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria is a parasitic disease that represents a public health problem worldwide. Protozoans of the Plasmodium genus are responsible for causing malaria in humans. Plasmodium species have a complex life cycle that requires post-translational modifications (PTMs) to control cellular activities temporally and spatially and regulate the levels of critical proteins and cellular mechanisms for maintaining an efficient infection and immune evasion. SUMOylation is a PTM formed by the covalent linkage of a small ubiquitin-like modifier protein to the lysine residues on the protein substrate. This PTM is reversible and is triggered by the sequential action of three enzymes: E1-activating, E2-conjugating, and E3 ligase. On the other end, ubiquitin-like-protein-specific proteases in yeast and sentrin-specific proteases in mammals are responsible for processing SUMO peptides and for deconjugating SUMOylated moieties. Further studies are necessary to comprehend the molecular mechanisms and cellular functions of SUMO in Plasmodium. The emergence of drug-resistant malaria parasites prompts the discovery of new targets and antimalarial drugs with novel mechanisms of action. In this scenario, the conserved biological processes regulated by SUMOylation in the malaria parasites such as gene expression regulation, oxidative stress response, ubiquitylation, and proteasome pathways, suggest PfSUMO as a new potential drug target. This mini-review focuses on the current understanding of the mechanism of action of the PfSUMO during the coordinated multi-step life cycle of Plasmodium and discusses them as attractive new target proteins for the development of parasite-specific inhibitors and therapeutic intervention toward malaria disease.